Information behaviour of Deaf people in university libraries: A pilot study - Coelho França, Maísa; Furnival, Ariadne Chloe Mary (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
In Brazil, there are more than 10 million Deaf people. Of these, 2,592 Deaf people are enrolled in Higher Education institutions. This pilot study aims to explore how the field of Library and Information Science (LIS) has studied Deaf people in university libraries. This research uses a mixed methods approach: the first part of the study uses a descriptive approach to present the current state of LIS literature on Deaf users of university libraries. The second part of the research is empirical and consists of a survey that has yet to be fully carried out. It also suggests how the university library can contribute to the empowerment of the deaf community.